Extras - Westerfeld, Scott (Westerfeld, Scott. Uglies, 2011)
After rebel Tally Youngblood brings down the uglies/pretties/specials regime, fame, instead of beauty, becomes the new world order, and fifteen-year-old Aya Fuse embarks on a dangerous plan to boost her popularity ranking.